The effect of individual innovativeness on critical thinking disposition in first and emergency aid program students - Pekince, Hatice; Aslan, Hakime (Annals of Medical Research, 2021)
Aim: This cross-sectional study aims to examine the effect of individual innovativeness on critical thinking disposition in first and emergency aid program students. Materials and Methods: The study was conducted between September and October 2019 with first and emergency program students studied in the 2018-2019 academic year. The population of the study was composed of students enrolled in the first and emergency aid program at Kovancılar Vocational School of Elazığ Fırat University. No sampling method was used in the study by aiming to reach the entire population. As a result, 95% of the population was reached, whereby a total of 121 students included in the study. Data were collected using an introductory information form, the Individual Innovativeness Scale (IIS), and the California Critical Thinking Disposition Inventory (CCTDI). Data were analyzed using the SPSS 23.0 package program and evaluated using percentage, mean, standard deviation, independent samples t-test, Mann Whitney U test, Kruskal-Wallis test, correlation analysis, and linear regression analysis. Results: The students’ IIS and CCTDI mean scores were 68.4±9.5 and 260.2±29.9, respectively. The individual innovativeness level of the students affected their critical thinking disposition. A statistically significant difference was found between the students’ individual innovativeness according to gender, status of keeping up with current issues and field-related developments, and status of believing in the necessity of using technological devices in education (p 0.05). Conclusion: As the individual innovativeness level of first and emergency program students increased, their critical thinking disposition increased.